Effect of Heat and Mass Transfer and Magnetic Field on Peristaltic Flow of a Fractional Maxwell Fluid in a Tube - F. S. Bayones; A. M. Abd-Alla; Esraa N. Thabet (Complexity)
Magnetic field and the fractional Maxwell fluids’ impacts on peristaltic flows within a circular cylinder tube with heat and mass transfer were evaluated while assuming that they are preset with a low Reynolds number and a long wavelength. The analytical solution was deduced for temperature, concentration, axial velocity, tangential stress, and coefficient of heat transfer. Many emerging parameters and their effects on the aspects of the flow were illustrated, and the outcomes were expressed via graphs. Finally, some graphical presentations were made to assess the impacts of various parameters in a peristaltic motion of the fractional fluid in a tube of different nature. The present investigation is essential in many medical applications, such as the description of the gastric juice movement of the small intestine in inserting an endoscope.